INVESTIGATING THE INDONESIAN EFL STUDENTS’ ARGUMENT IN ARGUMENTATIVE ESSAY - Dedi Turmudi (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2020)
This study investigates the written test results of the Indonesian undergraduate students’ argumentative essay. For that reason, three research questions are made. 1). what is the level of achievement of the students in the argumentative essay quantitatively? 2). what aspects of an essay appear in respect to the argumentative essay generic structure as formulated? 3). how well did they use the rhetoric reputation and argument in their essay?. 27 handwriting' answer sheets of undergraduate English Department students enrolled at semester four of a state university in Indonesia were taken purposively. The data analysis uses a quantitative and qualitative approach. The results show that the students quantitatively achieved average score 76,74 which means good. All parts of generic structures were expressed in different quality. However; the organization of the essay is the lowest part compared to the other four parts respectively content, vocabulary, and language use seen from their segmented scores. This study is confirmed to be inline the previous study in that the majority of the students did not present the refutation section in both their English essays. This implies that teachers should be more aware of promoting this absent aspect as this refutation or rebuttal is a distinguishing marker in argumentative and discussion essays.